Power Factor Correction based on Fuzzy Logic Controller with Fixed Switching Frequency - Kessal, A.; Rahmani, L.; Mostefai, M. (Elektronika ir Elektrotechnika, 2012)
This paper presents an application of different methods to regulate the output voltage of AC-DC converter associated with power factor corrector (PFC), a classical PI regulator was used, and another based on fuzzy logic was built, the both regulators were inserted in the voltage loop. To reduce the total harmonic distortion of the input current to give it a sinusoidal shape, hysteresis bands control were used, the variable band hysteresis give better results compared to other bands. All these controllers have been verified via simulation in Simulink and experimental test. The fuzzy logic inference based controller can achieve better dynamic response than its PI counterpart under large load disturbance and plant uncertainties. Furthermore, the variable hysteresis band control in the current loop gives a low THD of the input current compared to classical bands control. Ill. 12, bibl. 10, tabl. 2 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.118.2.1176